Pinalatuntunang kagamitan sa panimulang pagbasa sa Pilipino para sa mga estudyanteng Pangasinan - Ocsan, Elena C.
The purpose of the study is to make a programmed material for Pangasinan learners. The study is expected to help teachers in the field in teaching Pilipino so that a strong and solid foundation is established. It is also hoped that it will help solve the problem of lack of instructional materials and contribute to the Continuous Progression Scheme of the Bureau of Public Schools. In the preparation of the material, the linear model of programming is adopted. Results show that the three groups of learners learned to read at their own rate and abilities as shown in the following data: association of sound and symbol-92 percent, recognition of word-96 percent, comprehension-86 percent, and for the ability to read orally-93 percent.